Fachkräfte in der frühen Bildung: Erwerbssituation, Einstellungen und Änderungswünsche - Christa Katharina Spieß; Johanna Storck (Deutsches Institut für Wirtschaftsforschung (DIW), 2016)
– This report examines the labor market situation of those providing daycare or educational services to children primarily aged 6 or less in Germany. The analysis of these child daycare professionals is based on the German Socio-Economic Panel (SOEP) and the supplemental SOEP-study, 'Families in Germany' (FiD). The analysis contrasts the socio-demographic characteristics of child daycare professionals with those of comparable occupations. In addition to a comprehensive analysis of the employment situation of these child daycare professionals, their contentment, workloads, and preferences are also reviewed. The labor market preferences of child daycare professionals, based upon socio-demographic characteristics, personality traits, and family circumstances are analyzed. The study also evaluates if child daycare professionals experience excessive stress and strain in their work. To achieve this, we compare the self-evaluations of the child daycare professionals to those in comparable occupations. The results show that attitudes of child daycare professionals, which are also reflected within their personality, correspond highly with their occupational field. Although, child daycare professionals tend to have relatively high job satisfaction, they also face significant challenges in their day-to-day work. We do not find a 'gratification crisis' among the child daycare professionals, even though the burdens they experience are not trivial. It is noteworthy that many child daycare professionals feel that their employers underappreciate their efforts and that they lack career opportunities. Almost half of the child daycare professionals feel that their salary is inadequate.
Keywords: 330